El principio energía - Sacchi, Mario Enrique (Sapientia, 2008)
The author states that the conception of energy such as it has arrived to our time, has its origin in Ancient Greece, but the contemporary notion of energy includes many difficulties to be accepted without any criticism . In fact, physicists and philosophers disagree with its acope in the natural world, and, furthermore, with its entitative nature . Several opinion of psysico-mathematicians and philosophers are discussed in this article . However, in the final conclusion it is declared the need of a return to the aristotelian-thomistic theory which identifies energy with the act of being, now o f every wordly thing, now of separate substances, because God's proper act, which is his own essence, is nothing different from the energy conceived as the pure act of both Aristotle's and Aquinas ' metaphysics .